2009
DOI: 10.1016/j.jhazmat.2009.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Studies on toxicity of multi-walled carbon nanotubes on Arabidopsis T87 suspension cells

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
95
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(109 citation statements)
references
References 27 publications
2
95
0
Order By: Relevance
“…The activity variations of SOD, POD and CAT can be attributed to the hypersensitive response. Some studies have the similar opinions [16].…”
Section: Effect Of Go On the Activities Of Sod Pod And Cat In Tobaccmentioning
confidence: 79%
“…The activity variations of SOD, POD and CAT can be attributed to the hypersensitive response. Some studies have the similar opinions [16].…”
Section: Effect Of Go On the Activities Of Sod Pod And Cat In Tobaccmentioning
confidence: 79%
“…When contamination occurred through root exposure, both functionalized and non-functionalized CNTs have been reported to penetrate (Fig. 3) [85,93,94]. Then, CNTs are translocated to the upper part of plants by sharing the vascular system with water and nutrients and they can be transported via transpiration (Fig.…”
Section: Fate and Impacts Of Carbon Nanotubes On Plantsmentioning
confidence: 99%
“…3) [85,93,94]. Lin et al [93] studied the intergenerational transfer of carbon nanomaterials (carbon nanoparticles C 70 and MWCNTs 40e70 nm diameter) in rice (Oryza sativa L. ssp. japonica, cv Taipei 309).…”
Section: Fate and Impacts Of Carbon Nanotubes On Plantsmentioning
confidence: 99%
“…In an evaluation of environmental influence, Lin et al 94) evaluated the toxicity for insects (drosophila). MWCNTs showed low toxicity for larval and adult drosophila.…”
Section: Multi-walled Carbon Nanotubes (Mwcnts)mentioning
confidence: 99%
“…Kang et al 34) reported the microbial cytotoxicity for SWCNTs, MWCNTs, and C60, and the tendency was different between the Gram-positive and Gram-negative microbes. Lin et al 94) reported that MWCNTs suppress the cell viability of plant cells (Arabidopsis). These results suggest that the environmental influence of MWCNTs should be a concern, especially because mass production of MWCNTs has started in recent years.…”
Section: Multi-walled Carbon Nanotubes (Mwcnts)mentioning
confidence: 99%